In Vitro Cytotoxicity Assessment of an Orthodontic Composite Containing Titanium-dioxide Nano-particles - Farzin Heravi (Journal of Dental Research, Dental Clinics, Dental Prospects, 2013)
Background and aims. Incorporation of nano-particles to orthodontic bonding systems has been considered to prevent enamel demineralization around appliances. This study investigated cytotoxicity of Transbond XT adhesive containing 1 wt% titanium dioxide (TiO2) nano-particles. Materials and methods. Ten composite disks were prepared from each of the conventional and TiO2-containg composites and aged for 1, 3, 5, 7 and 14 days in Dulbecco’s Modified Eagle’s Medium (DMEM). The extracts were obtained and exposed to culture media of human gingival fibroblasts (HGF) and mouse L929 fibroblasts. Cell viability was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Results. Both adhesives were moderately toxic for HGF cells on the first day of the experiment, but the TiO2-containing adhesive produced significantly lower toxicity than the pure adhesive (P<0.05). No significant differences were found in cell viability percentages between the two groups on the other days (P>0.05). There was a significant reduction in cell toxicity with increasing pre-incubation time (P<0.001). L929 cells showed similar toxicity trends, but lower sensitivity to detect cytotoxicity of dental composites. Conclusion. The orthodontic adhesive containing TiO2 nano-particles indicated comparable or even lower toxicity than its nano-particle-free counterpart, indicating that incorporation of 1 wt% TiO2 nano-particles to the composite structure does not result in additional health hazards compared to that occurring with the pure adhesive.